2010
DOI: 10.1016/j.jcrs.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spherical intraocular lens implantation and conventional laser in situ keratomileusis on peripheral ocular aberrations

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Mathur et al studied the optical quality after OK [ 10 ] and LASIK [ 20 ]. They performed measurements across the 42° horizontal vs 32° vertical central visual field in samples of 3 (OK) and 6 (LASIK) subjects and observed an increase of high-order aberration at peripheral locations after both treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathur et al studied the optical quality after OK [ 10 ] and LASIK [ 20 ]. They performed measurements across the 42° horizontal vs 32° vertical central visual field in samples of 3 (OK) and 6 (LASIK) subjects and observed an increase of high-order aberration at peripheral locations after both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Ehsaei et al [ 42 ] studied refractive error across four meridians in healthy myopic subjects and emmetropes and they obtained comparable results with eccentricity-dependent profile, to the overall eccentricities studied, such as shown by Shen et al [ 43 ]. Most of the previous studies with respect to the refractive profile before and after refractive treatments only reported results from the horizontal meridian [ 9 , 17 ] or horizontal and vertical meridians [ 10 , 20 , 32 ]. Autorefractometers were mostly used [ 9 11 , 17 ], but wavefront sensors [ 10 , 20 ] were also introduced in this kind of evaluation since there was a good correlation between autorefractometers and Hartmann-Shack aberrometer values [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The higher-order aberrations also have received attention in the last dozen years. [4][5][6][7][8][9][10][11][12][13][14][15][16] Investigations of on-axis (foveal) aberrations assume circular pupils, and for most eyes this is a reasonable approximation. 17 A set of circular polynomials, such as Zernike polynomials, is used to describe the wavefronts, and the refractions may be obtained from the coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Previous theoretical work 15,16 predicted an increase in peripheral astigmatism in pseudophakic eyes due to the intraocular lens (IOL) design. A more recent experimental study 17 also showed a tendency toward more myopic spherical equivalents (SEs) in the periphery at G20 degrees relative to the fovea in eyes implanted with IOLs compared with normal phakic eyes. Although cataract surgery attempts to minimize foveal refractive errors after removing the cataractous lens, peripheral refractive errors might require closer consideration for the reasons listed above.…”
mentioning
confidence: 97%